Reconstruction of Legality Principles in the Function of Protection of Victims - Setyawan, Vincent Patria; Widiartana, Gregorius (Universitas Suryakancana, 2021)
AbstractThe principle of legality currently in effect in Indonesia still has weaknesses when faced with actions that are included in the Crimina Extra Ordinary which cannot be reached by the legality principle. The problem that arises is that the act causes harm to the victim, and the perpetrator cannot be convicted. This problem is formulated in the question: how are the limitations of the legality principle related to the protection function for victims? how is the construction of the ideal legality principle in providing protection for victims? The writing of this article uses normative legal research that discusses the legality principle as the basis for the implementation of punishment using a conceptual approach to the legality principle. The analysis technique used is deductive analysis technique, with the nature of prescriptive analysis. The result of this research is the concept of extending the legality principle that provides equal protection for the perpetrators and victims of crime to replace the current formulation of the legality principle, which does not have a protection function for crime victims.Keywords: Limited of Legality Principles, Protection Functions, Crime Victims